Pendidikan Alquran Berbasis Budaya Melayu Dan Iptek Di MAN 2 Langkat Tanjung Pura Kabupaten Langkat - Maulida Maulida; Fatimah Ahmad; Nur Salimi (Journal on Education, 2024)
This research aims to she how koran education is based on malay culture and science and technology in Man 2 Langkat , Langkat Distrcik. We know that knowledge is hinted at by Allah in the Koran in the form of raising the level of people who have knowlwdge and it is imposibble to achieve progress (desire) to function this nature well without the power. Science and technology is a means for humanity to always be able to color to maly culture that exists in Langkat. Science and technology is a person’s advanced knowledge and is able to be a tool for solving problems. It is something that no one can leave behind because it is very important. This is often mentioned in the Koran , meaning that Islam strongly recommends the development of science and technology. The link between Malay culture based Koranic education and science ad technology is that the Koran views education as the first and main issue in developing and improving the condition of humanity in the world. The teachings contained therein include faith, monotheism, noble morals, and rules regarding vertical and horizontal relationships which are instilled through education based on Malay culture and science adan technology.In this research, the author provides how to direct and guide children through alquran and science and technology education which is currently developing very rapidly. Malay culture is a step towards maintaining the existing culture in teaching children about Alquran education. Where there are still many parent educating their children to recite the Koran in the afternoon in the villages to get alquran education. As the development of science and technology progresses, it does not become an obstacle for children to receive alquran education.As for the method used in this research, this researcha uses a descriptive qualitative approach, with a qualitative approach. With a qualitative approach, researchers will look at the malay cultural phenomenon in Man 2 Langkat as a forum for implementing formal education. The qualitative selection in this research objectives that want to be described, namely to reveal Alquran education, the development of Malay culture, the implementation of science and technology development on the character of student in the second world. This reason is very correct and appropriate considering the nature of the qualitative research process which involves important efforts such as asking questions and producedures, collecting specific data and interpreting the meaning of the data.